Complexos de Cu(II) de algumas fluorquinolonas: sínteses, atividade anti-T.cruzi e investigação do mecanismo de ação - Darliane Aparecida Martins (2011)
Chagas disease, caused by the Trypanosoma cruzi protozoa, is an endemic parasitosis which affects about 12 million people in Latin America. The only two available drugs for the treatment of Chagas disease are Nifurtimox and Benznidazole, but both exhibit grave side effects. The limitations of the current chemotherapy for this illness justify the search for new drug candidates that could be effective and selectiveagainst this parasite, but with low toxicity and low costs. Fluorquinolones are an important class of synthetic antibacterial agents whose anti-parasitic activity was reported in the literature, especially against the Leishmania panamensis. Taking into account that metal complexes could be more active that their free ligands, in this work we prepare Cu(II) complexes of norfloxacin (NOR), levofloxacin (LEVO) and sparfloxacin (SPAR), containing or not pyridine (py), 2,2- bipyridine (bipy) or 1,10-phenantholine as co-ligands. The complexes were evaluatedfor their ability to suppress in vitro the growth of tripomastigote forms of Trypanosoma cruzi. Twelve new complexes were obtained: [CuCl2(H2O)(L)], [CuCl2(py)(L)], [CuCl(bipy)(L)]Cl and [CuCl2(fen)(L)] (L = NOR, LEVO e SPAR). In all cases the ligands coordinate with the metal centre via both the pyridone and one carboxylate oxygen in the neutral zwitterionic form. Complexes containing 1,10-phenanthroline asco-ligands revealed to be the most active among all studied compounds.The interaction of the complexes with DNA has been investigated using UV-vis spectroscopy. The affinity of the complexes with bovine serum albumin (BSA) was also investigated using fluorescence spectroscopy, since this protein is responsible for drug transportation in mammals. The intrinsic biding constants for drug-DNA interactions were found in the 103 a 105 M-1 range and are supposed to be due to intercalation withcleavage of the secondary structure of DNA. The binding constants for drug-BSA interaction were found in the 105 e 106 M-1 range, i.e., the studied compounds are revealed to have more affinity with BSA.In short, with this work we believe to have contributed to a better understanding not only of the fluorquinolones and their metal complexes chemistry, but of their antiparasitic properties as well.